PENGARUH KETERAMPILAN MEMBACA PEMAHAMAN TERHADAP HASIL BELAJAR SUBTEMA MANUSIA DAN LINGKUNGAN - Widiya Wahyu; Yuli Mulyawati; Stella Talitha (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is based on quantitative research with a causal approach, which aims to identify the effect of reading comprehension skills on students’ learning outcomes in the human and environment subtheme at the fifth-grade students of SDN Batutulis Bogor. The techniques used were tests and questionnaires. The population was 84 students with a total sample of 46 students. The research was conducted in the odd semester of the 2022/2023 academic year. The results showed that the effect of reading comprehension skills on students’ learning outcomes of the human and environmental subthemes was shown by statistical analysis that produced a correlation coefficient rxy of 0.49. It shows that there was an effect between reading comprehension skills and students’ human and environmental subthemes. While the coefficient of determination (r2) was 24.01%. The rest of 75.99% was determined by other factors. The average students’ learning outcomes on the human and environmental subthemes at 24.01% were determined by reading comprehension skills through the regression equation = 11.15 + 0.52X, which means that every improvement in the unit value of reading comprehension skills will influence students’ learning outcome in the human and environmental subthemes at 0.52 units.